8) E

G = 5 + √7 (9 – R)² + 9

G – 5 = √7 (9 – R)² + 9

Squaring both sides,

(G – 5)² = 7 (9 – R)² + 9

(G – 5)² – 9 = 7 (9 – R)²

(G – 5)² – 9 = (9 – R)²
         7

Square Rooting on both sides, 


(G – 5)² – 9 = 9 – R
            7

{√(G – 5)² – 9} – 9 =  – R
             7

To change the sign of R from negative to positive, we need to multiply both sides by -1

(-1) x {√(G – 5)² – 9} – 9 =  – R (-1)
                       7

R = 9 – {√(G – 5)² – 9} 
                       7


So the answer is E.